2014
DOI: 10.1186/1471-2105-15-s6-s2
|View full text |Cite
|
Sign up to set email alerts
|

Selection of entropy-measure parameters for knowledge discovery in heart rate variability data

Abstract: BackgroundHeart rate variability is the variation of the time interval between consecutive heartbeats. Entropy is a commonly used tool to describe the regularity of data sets. Entropy functions are defined using multiple parameters, the selection of which is controversial and depends on the intended purpose. This study describes the results of tests conducted to support parameter selection, towards the goal of enabling further biomarker discovery.MethodsThis study deals with approximate, sample, fuzzy, and fuz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 35 publications
3
70
0
Order By: Relevance
“…It could be suggested that the selection of m between 1 and 2 and r between 0.10 and 0.25 in FuzzyMEn would probably yield fine classification results between NSR and CHF groups. This result supports our hypothesis that FuzzyMEn would demonstrate better relative consistency as compared to SampEn and agrees the previous conclusion that the selection of r for SampEn appears to be more difficult than the selection of m [10,11,18].Typically it is suggested that for clinical data, m is to be set at 2 for SampEn [2,12]. Besides, an m of 3 has been found to be acceptable for SampEn in [8].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…It could be suggested that the selection of m between 1 and 2 and r between 0.10 and 0.25 in FuzzyMEn would probably yield fine classification results between NSR and CHF groups. This result supports our hypothesis that FuzzyMEn would demonstrate better relative consistency as compared to SampEn and agrees the previous conclusion that the selection of r for SampEn appears to be more difficult than the selection of m [10,11,18].Typically it is suggested that for clinical data, m is to be set at 2 for SampEn [2,12]. Besides, an m of 3 has been found to be acceptable for SampEn in [8].…”
Section: Discussionsupporting
confidence: 79%
“…This is especially true for studies with pathological populations that are limited in their clinical measurement. However, caution has been advised when using time series of less than 200 points for either ApEn or SampEn [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can take multiple values and so provides multiple measures. Previous work has compared several entropy measures in terms of their efficacy in distinguishing congestive heart failure and arrhythmia from normal sinus rhythm [13]. However in this work we aim to compare two commonly applied multiscale entropy measures and MFDFA, and focus on a single morbidity, CAN, in its early and later stages in asymptomatic individuals with no cardiovascular disease or diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on fuzzy set theory, to measure the complexity of the time series data, fuzzy entropy (FuzzyEn) [22] was introduced. FuzzyEn is a modified algorithm of sample entropy (SampEn) [23][24][25][26][27]. Since then, FuzzyEn has been successful in feature extraction.…”
Section: Introductionmentioning
confidence: 99%